GAMBARAN NILAI RASIO NEUTROFIL TERHADAP LIMFOSIT PADA PASIEN INFARK MIOKARD AKUT YANG DIRAWAT INAP DI RSUD ABDOEL WAHAB SJAHRANIE SAMARINDA PERIODE TAHUN 2022: DESCRIPTION OF THE NEUTROPHIL TO LYMPHOCYTE RATIO VALUE IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION HOSPITALIZED AT ABDOEL WAHAB SJAHRANIE HOSPITAL SAMARINDA IN THE PERIOD OF 2022 - Manalu, Pangeran Mangaraja; Magdaleni, Agustina Rahayu; Rajibsman (ITKES Wiyata Husada Samarinda, 2025)
Acute myocardial infarction is an irreversible myocardial necrosis characterized by a significant increase in cardiac biomarkers due to prolonged ischemia. In addition to the necrotic process, there is an acute inflammatory process occurs during acute myocardial infarction, which is dominated by neutrophils and lymphocytes, made the neutrophyl-to-lymphocyte ratio a potential inflammation biomarker. This research aim to observed the neutropil-to-lymphocytes ratio in patients with acute myocardial infarction at Abdoel Wahab Sjahranie Hospital Samarinda during the 2022 period. The study employed a retrospective descriptive method with purposive sampling. The research sample included 83 patients diagnosed with acute myocardial infarction at Abdoel Wahab Sjahranie Hospital Samarinda during 2022 period. The total sample were 83 people who has fulfilled the inclusion and exclusion criteria. The study reveals that the mean neutrophil-to-lymphocyte ratio in patients with acute myocardial infarction is 5,37, with the lowest value at 0,85 and the highest at 27,11. Additionally, 30 patients were diagnosed with ST Elevation Myocardial Infarction (STEMI) and 53 patients with Non ST Elevation Myocardial Infarction (NSTEMI). The majority of patients (56,6%) had a neutrophil-to-lymphocyte ratio >3,53 with the least distribution in category of <1,73 were 10 patients (12,0%).